Analisis Korelasi Antara Nilai Kepadatan (Sand Cone) dan Daya Dukung (Field CBR) pada Material Timbunan Reklamasi (Studi Kasus: Pelabuhan Patimban Paket 6) - Dhani Rulianto; Ingrid Multi Rezeki (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
Quality control in the Package 6 Patimban Port reclamation project greatly determines the stability of port operations. This study aims to analyze the correlation between the average soil density (Sand Cone) of layers 1–7 to the surface bearing capacity (Field CBR) of the subgrade and formulate a prediction model. Using a quantitative approach, this study analyzed 26 samples using simple linear regression without a constant (regression through the origin). The results of the analysis showed a very strong and positive correlation relationship with the value of R = 0.976. The resulting prediction model is Y = 0.141X with a coefficient of determination (R2) of 0.953. This proves that 95.3% of the variation in Field CBR values is significantly influenced by the average density of all layers of the landfill. These findings confirm that every 1% increase in average density increases the Field CBR by 0.141%.